Trends in all-cause pneumonia and otitis media in children aged <2 years following pneumococcal conjugate vaccine introduction in Colombia (2020)
In Colombia, pneumococcal conjugate vaccines (PCVs) were implemented into the infant universal mass vaccination program in a stepwise manner; PCV-7 between 2009 and 2011 in different geographic regions/cities, with nationwide introduction of a 10-valent vaccine (PHiD-CV) in 2012. We aimed to describe trends in all-cause pneumonia mortality and overall mortality, and in the incidence of all-cause pneumonia and otitis media (OM) in Colombian children <2 y (y = years) of age, before and after PCV introduction. We obtained mortality and incidence data, nationally and for five major cities (Bogota, Medellin, Barranquilla, Cali and Cartagena) from 2005–2016 and 2008–2016, respectively, comparing mortality and incidence proportions in the post-PCV introduction period with those in the pre-PCV period. Overall mean reductions in all-cause pneumonia mortality was observed in the post-PCV period nationally (48.8%; 95%CI: 45.5–51.8%) and in four cities including Bogota (77.1%; 71.1–81.8%) and Medellin (56.4%; 44.1–65.9%); no substantial reduction was observed in Cartagena. Similar findings were observed for overall mortality. Reductions in all-cause pneumonia incidence were observed in Bogota (66.0%; 65.5–66.6%), Medellin (40.6%; 39.3–41.9%) and Cartagena (15.0%; 11.2–18.6%), while incidence increased in Barranquilla (78.5%; 68.4–89.2%) and Cali (125.5%; 119.2–132.0%). All-cause OM incidence fell in Medellin and Bogota (42.1–51.1%) but increased (95.8%) in Barranquilla. In conclusion, overall reductions in disease outcomes were observed following PCV introduction in most cities and nationwide. Decreasing trends in outcomes were observed prior to PCV introduction, and limited data points and data reporting issues may have influenced our results. (ClinicalTrials.gov: NCT02567747)